Genomic erosion in a demographically recovered bird species during conservation rescue. Issue 4 (12th May 2022) - Jackson, Hazel A.; Percival‐Alwyn, Lawrence; Ryan, Camilla; Albeshr, Mohammed F.; Venturi, Luca; Morales, Hernán E.; Mathers, Thomas C.; Cocker, Jonathan; Speak, Samuel A.; Accinelli, Gonzalo G.; Barker, Tom; Heavens, Darren; et al.
Abstract: The pink pigeon ( Nesoenas mayeri ) is an endemic species of Mauritius that has made a remarkable recovery after a severe population bottleneck in the 1970s to early 1990s. Prior to this bottleneck, an ex situ population was established from which captive‐bred individuals were released into free‐living subpopulations to increase population size and genetic variation. This conservation rescue led to rapid population recovery to 400–480 individuals, and the species was twice downlisted on the International Union for the Conservation of Nature (IUCN) Red List. We analyzed the impacts of the bottleneck and genetic rescue on neutral genetic variation during and after population recovery (1993–2008) with restriction site‐associated sequencing, microsatellite analyses, and quantitative genetic analysis of studbook data of 1112 birds from zoos in Europe and the United States. We used computer simulations to study the predicted changes in genetic variation and population viability from the past into the future. Genetic variation declined rapidly, despite the population rebound, and the effective population size was approximately an order of magnitude smaller than census size. The species carried a high genetic load of circa 15 lethal equivalents for longevity. Our computer simulations predicted continued inbreeding will likely result in increased expression of deleterious mutations (i.e., a high realized load) and severe inbreeding depression. Without continued conservation actions, it is likely that the pink pigeon will go extinct in the wild within 100 years. Conservation rescue of the pink pigeon has been instrumental in the recovery of the free‐living population. However, further genetic rescue with captive‐bred birds from zoos is required to recover lost variation, reduce expression of harmful deleterious variation, and prevent extinction. The use of genomics and modeling data can inform IUCN assessments of the viability and extinction risk of species, and it helps in assessments of the conservation dependency of populations. Resumen: La paloma rosada ( Nesoenas mayeri ) es una especie endémica de Mauricio que se ha recuperado impresionantemente después de un grave cuello de botella poblacional a principios de la década de 1970 que duró hasta inicios de la década de 1990. Antes de este cuello de botella se había establecido una población ex situ de la cual se liberaban individuos reproducidos en cautiverio a las subpoblaciones en libertad para incrementar la variación genética y el tamaño poblacional. Este rescate de conservación derivó en una recuperación rápida de la población (400‐480 individuos) y la especie cambió positivamente de categoría dos veces en la Lista Roja de la Unión Internacional para la Conservación de la Naturaleza (UICN). Analizamos los impactos del cuello de botella y el rescate genético sobre la variación genética neutral durante y después de la recuperación poblacional (de 1993 a 2008) mediante secuenciación RAD, análisis de microsatélites y análisis genéticos cuantitativos de los datos del libro genealógico de 1112 aves ubicadas en zoológicos de Europa y los Estados Unidos. Usamos simulaciones por computadora para estudiar los cambios pronosticados en la variación genética y en la viabilidad poblacional del pasado hacia el futuro. La variación genética declinó rápidamente, a pesar de la recuperación poblacional, y el tamaño efectivo de la población fue aproximadamente un orden de magnitud más pequeño que el tamaño del censo. La especie contó con una carga genética elevada de casi 15 equivalentes letales para la longevidad. Nuestras simulaciones pronostican que la endogamia continua probablemente resultará en un incremento en la expresión de mutaciones deletéreas (es decir, una carga realizada elevada) y en una depresión endogámica severa. Sin acciones continuas para la conservación, es probable que la paloma rosada esté extinta en vida libre dentro de cien años. El rescate de conservación de la paloma rosada ha sido fundamental en la recuperación de la población silvestre; sin embargo, se requiere de un rescate genético adicional con las aves de reproducción en cautiverio de los zoológicos para recuperar la variación perdida, reducir la expresión de la variación deletérea dañina y prevenir la extinción. El uso de la genómica y los datos modelados puede orientar las valoraciones de la UICN sobre la viabilidad y el riesgo de extinción de las especies, además de que ayuda en la evaluación de la dependencia que tienen las poblaciones de la conservación.